Random amplified polymorphic DNA (RAPD) profiling of planted sago palm - Allysya Sylvinessa, anak Alvin (Universiti Malaysia Sarawak, UNIMAS, 2013)
Sago palm (Metroxylon sagu) is one of the commercially important palm species in Sarawak. They can occupy a diversity of habitats at different altitudes but they show dominancy for wet habitats. Sago palm is widely planted in Sarawak due to its commercial value. The objective of study is to isolate genomic DNA from planted sago palm and to obtain DNA band profiles of the sago palm using the RAPD method. The DNA extraction of the sago palm was conducted using common CTAB extraction method. This CTAB method for DNA extraction of fresh tissue has been successfully used in laboratory for wide variety of plant families. RAPD-PCR is a method which randomly amplifies genomic DNA utilising single, short and arbitrary oligonucleotide primers. It is a fast and easy to perform since no prior knowledge on the target sequence is needed. The DNA band profiles were observed via agarose gel electrophoresis analysis. In this study, a good quality and yield of sago palm genomic DNA was extracted. Also, DNA band profiles for sago palm were successfully generated using RAPD commercial decamer primers.